EFEKTIVITAS PENERAPAN MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA POP-UP BOOK DALAM MENGEMBANGKAN KEMAMPUAN BERPIKIR KRITIS GEOMETRI RUANG SISWA DI SD NEGERI GUGUS KI HAJAR DEWANTARA PEMALANG - Tri Rahmawati, Sulistyani; Andrijati, Noening (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to examine the effectiveness of the Project Based Learning Model assisted by Pop-Up Book Media in terms of learning outcomes of grade V mathematics in elementary schools. This research is a type of Quasi Experimental Design, with a Nonequivalent Control Group Design. The samples of this study were fourth grade students of SDN 01 Gondang and fourth grade students of SDN 02 Gondang, Taman District, Pemalang Regency consisting of 2 classes, namely 32 students of SDN 01 Gondang and 31 students of SDN 02 Gondang. Each class had the same ability before being given treatment. After being given treatment, the experimental class has an average difference in learning outcomes with the control class, this is evidenced by the hypothesis test, namely the obtained tcount value is more than the ttable value of 7.310> 1.999 that Ho is rejected or there is a difference in student learning outcomes between those using the PjBL model assisted by pop-up book media and those using conventional approaches and the t test that the tcount value> ttable (37.374> 1.714) and the significance value <0.05 (0.000 <0.05), so that Ho2 is rejected. So it can be concluded that the Project Based Learning Model assisted by Pop-Up Book Media is effectively applied to mathematics learning in elementary schools.